Activation of murine RNase L by isopolar 2'-phosphonate analogues of 2',5' oligoadenylates - Páv, Ondřej; Protivínská, Eva; Pressová, Martina; Collinsová, Michaela; Jiráček, Jiří; Snášel, Jan; Masojídková, Milena; Buděšínský, Miloš; Rosenberg, Ivan (Journal of medicinal chemistry, 2006)
To determine the influence of methylene group insertion in the internucleotide linkage on the binding process of 2',5'-oligoadenylates to RNase L, a series of 2'-phosphonate-modified trimers and tetramers were synthesized from appropriate monomeric units and evaluated for their ability to bind to murine RNase L. Tetramers pAAXA modified by ribo-, arabino-, or xylo-2'-phosphonate unit X in the third position were capable of binding to RNase L in nanomolar concentrations. The replacement of the first residue (pXAAA), or both the first and the third residues (pXAXA), was also tolerated by the enzyme. In contrast, in all cases, the replacement of the second residue (pAXAA) resulted in the significant decrease of binding ability. Additionally, no more than two phosphonate modifications in the tetramer were allowed to retain the binding affinity to the enzyme. Although all three tetramers pAAXA were found to be potent enzyme binders, only tetramers modified by ribo- and xylo-2'-phosphonate unit X activated the RNase L-catalyzed cleavage of the RNA substrate. Surprisingly, tetramer pAAXA, modified by arabino-2'-phosphonate unit X, did not activate the enzyme and can be considered a potent antagonist. In comparison with their natural counterpart, the phosphonate analogues of the pA4 exhibit superior resistance toward nucleases present in the murine spleen homogenate.
Keywords: financování organizované; Animals; Oligoribonucleotides; slezina; Adenine Nucleotides; In Vitro Techniques; endoribonukleasy; vazba proteinů; Structure-Activity Relationship; techniky in vitro; Endoribonucleases; Mice; Stereoisomerism; stereoizomerie; adeninnukleotidy; Mice, Inbred BALB C; myši; Financing, Organized; organofosfonáty; Male; myši inbrední BALB C; Spleen; oligoribonukleotidy; vztahy mezi strukturou a aktivitou; zvířata; mužské pohlaví; Protein Binding; Organophosphonates